2002
DOI: 10.1126/science.1079107
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Strongly Interacting Degenerate Fermi Gas of Atoms

Abstract: We report on the observation of a highly-degenerate, strongly-interacting Fermi gas of atoms. Fermionic 6 Li atoms in an optical trap are evaporatively cooled to degeneracy using a magnetic field to induce strong, resonant interactions. Upon abruptly releasing the cloud from the trap, the gas is observed to expand rapidly in the transverse direction while remaining nearly stationary in the axial. We interpret the expansion dynamics in terms of collisionless superfluid and collisional hydrodynamics. For the dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

63
1,162
0
24

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 982 publications
(1,250 citation statements)
references
References 26 publications
63
1,162
0
24
Order By: Relevance
“…For free fermions ξ = 1, but for strongly correlated fermions the theory contains no obvious expansion parameter and the determination of ξ is a difficult non-perturbative problem. Recent interest in this problem has been fueled by experimental advances in creating cold, dilute gases of fermionic atoms tuned to be near a Feshbach resonance [15]. These experiments are beginning to yield results for the equation of state of non-relativistic fermions in the limit |k F a| → ∞.…”
Section: Introductionmentioning
confidence: 99%
“…For free fermions ξ = 1, but for strongly correlated fermions the theory contains no obvious expansion parameter and the determination of ξ is a difficult non-perturbative problem. Recent interest in this problem has been fueled by experimental advances in creating cold, dilute gases of fermionic atoms tuned to be near a Feshbach resonance [15]. These experiments are beginning to yield results for the equation of state of non-relativistic fermions in the limit |k F a| → ∞.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the s-wave phase shift satisfies δ(k) = π/2 for all k and the field theory describing the many-body system is at a conformal fixed point 1 ; in 1998 it was suggested that unitary fermions could serve as the starting point for an effective field theory expansion for nuclear physics [2,3]. Since then the unitary fermion gas has been created and studied experimentally by trapping atoms tuned to a Feshbach resonance by means of an applied magnetic field, exhibiting collective effects interpolating between the well understood phenomena of BCS pairing and Bose-Einstein condensation [4][5][6][7][8][9][10][11][12][13]. The nonperturbative nature of the strongly coupled interaction between unitary fermions poses a nontrivial challenge for theory, and numerical simulation has played an essential role in making progress.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate paper [6], we have calculated the equation of state of low-density neutron matter using the virial expansion, in order to assess quantitatively how close the system is to universal behavior at finite temperature. The equation of state of resonant and dilute Fermi gases has also been studied in laboratory experiments with trapped atoms [7,8,9,10], and Ho et al have used the virial expansion to describe Fermi gases at high temperatures in the vicinity of Feshbach resonances [11,12].…”
Section: Introductionmentioning
confidence: 99%